The Bible and ecology - Rolston, Holmes, 1932-2025, author; Union Theological Seminary in Virginia, publisher (Colorado State University. Libraries, 1996)
The Bible is not a book of ecology. It does recommend a human ecology, accentuating life in justice and love that makes possible a good (righteous), long (sustainable) life in a promised, promising land. Contemporary readers encounter claims about how to value nature, the earthen genesis with intrinsic goodness, blessed by God. That vision is biocentric, anthropocentric, and theocentric. The Hebrew scriptures can be a catalyst in our ecological crisis.
Keywords: natural value; environmental ethics; The Bible; ecological science; human values; ecology